DUKUNGAN ORANG TUA DAN MOTIVASI BELAJAR PADA SISWA SMA YANG MEMPERSIAPKAN SELEKSI BERSAMA MASUK PERGURUAN TINGGI NEGERI (SBMPTN) - Zafirah Nursyta Wijaya; elisabet widyaning hapsari (Jurnal Psikologi Malahayati, 2022)
ABSTRACT: PARENTAL SUPPORT AND LEARNING MOTIVATION IN HIGH SCHOOL STUDENTS PREPARING FOR SBMPTN Students who want to follow the joint selection path to enter state universities must have the motivation to learn within themselves. Motivation learning is an internal or external drive for individuals to change their behavior, which is learning to achieve the planned goals. Increasing students' learning motivation, can be influenced by external factors, one of them is family factors, attention from parents, and a peaceful home atmosphere that will support children's learning enthusiasm. The family factor that is intended to increase children's learning motivation is support from parents. The objective of this research was to determine the relationship between parental support and learning motivation in students who are preparing for the joint selection path for state universities (SBMPTN). This research involved 121 participants of 12th grade high school students in Surabaya who will continue to state universities through the SBMPTN path. The sampling used was purposive sampling and snowball sampling. Data retrieval used a scale of parental support and learning motivation compiled by the researcher. This research used Kendall's Tau-B non-parametric statistics. The results showed that there was a significant relationship between parental support and learning motivation in students preparing for joint selection to enter state universities (r (119) = .384, p = .000). The higher the parental support, the higher the learning motivation, and vice versa, the lower the parental support, the lower the learning motivation. Based on this, parental support for children’s learning motivation is very influential, because with parental support it can make children motivated and serious in their learning activities. Keywords: High School Students, Learning Motivation, Parental Support Motivasi belajar merupakan dorongan internal ataupun eksternal pada diri individu untuk melakukan perubahan tingkah laku yaitu belajar agar mencapai tujuan yang telah direncanakan. Dalam meningkatkan motivasi belajar pada diri siswa dapat dipengaruhi dari faktor eksternal salah satunya adalah faktor keluarga, perhatian dari orang tua, serta suasana rumah yang tentram akan menunjang semangat belajar anak. Tujuan dari penelitian ini yaitu untuk mengetahui ada atau tidaknya hubungan antara dukungan orang tua dengan motivasi belajar pada siswa yang mempersiapkan seleksi bersama masuk perguruan tinggi negeri (SBMPTN). Penelitian ini melibatkan 121 partisipan siswa SMA kelas 12 di Surabaya yang akan melanjutkan ke perguruan tinggi negeri melalui jalur SBMPTN. Pengambilan sampel yang digunakan yaitu purposive sampling dan snowball sampling. Pengambilan data menggunakan skala dukungan orang tua dan motivasi belajar yang disusun sendiri oleh peneliti. Penelitian ini menggunakan statistik non-parametrik Kendall’s Tau-B. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara dukungan orang tua dengan motivasi belajar pada siswa yang mempersiapkan seleksi bersama masuk perguruan tinggi negeri (r (119) = .384, p = .000). Semakin tinggi dukungan orang tua maka semakin tinggi pula motivasi belajar, begitu juga sebaliknya semakin rendah dukungan orang tua maka semakin rendah pula motivasi belajar. Melihat hal tersebut dukungan orang tua terhadap motivasi belajar anak sangat mempengaruhi, karena dengan adanya dukungan orang tua dapat menjadikan anak termotivasi serta bersungguh-sungguh dalam kegiatan belajarnya. Kata kunci: Siswa SMA, Motivasi Belajar, Dukungan Orang Tua